CONSTRAINTS AND SUGGESTIONS OF THE RAWEP FUNCTIONARIES FOR EFFECTIVE IMPLEMENTATION OF RAWEP - B.NAVEEN*, T. GOPIKRISHNA and B. MUKUNDA RAO, (The Journal of Research ANGRAU, 2019)
The study was conducted to analyse the constraints faced by the RAWEP functionaries of ANGRAU andsuggestions of the RAWEP functionaries for the effective implementation of RAWEP. The most important constraintsfaced by the RAWEP functionaries were: non- coincidence of RAWEP with crop season, difficulty in providing girlstudents accommodation, traditional nature of external evaluation, low stipend amount to students, inadequatebudget allocation for training programmes and field visits, lack of seriousness, dedication and punctuality amongthe students, last minute selection of host farmers and villages, allotment of more number of students to eachDAATTC and unequal involvement of the all faculty in RAWEP. Suggestions offered by RAWEP functionaries includestimely payment of RAWEP stipend, coinciding RAWEP with crop season, adequate staffing arrangement at DAATTC/KVKs, reducing work load of scientists looking after RAWEP at DAATTC/KVKs, advance selection of RAWEP villageand providing updated knowledge on crop protection.